2022
DOI: 10.1177/02698811221078751
|View full text |Cite
|
Sign up to set email alerts
|

The cortical silent period in schizophrenia: A systematic review and meta-analysis focusing on disease stage and antipsychotic medication

Abstract: Background: Although numerous studies reported some changes of cortical silent period (CSP), an indicator of gamma-aminobutyric acid (GABA) function in central nervous system, in schizophrenia patients, it has been unknown how the disease stage and antipsychotic medication affect CSP values. Methods: The present study conducted a systematic review of previous literature comparing CSP between schizophrenia patients and healthy subjects, and then performed meta-analysis on the effects of (1) the disease stage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Keedy et al (2009) also found an increase in bilateral supplementary eye fields, left frontal eye fields, and bilateral cerebellum functional activity during visual attention and sensorimotor tasks and a decrease activity in other distributed brain regions in patients treated with risperidone, ziprasidone, or haloperidol. Miyazawa et al (2022) noted that that clozapine prolongs cortical silent period (the interruption of voluntary muscle contraction following a motor-evoked potential triggered by transcranial magnetic stimulation over the primary motor cortex) due to increase GABA transmission with GABA B receptors. Sarpal et al (2015) examined the association between antipsychotic treatment (e.g., aripiprazole or risperidone) and activity changes in striatal areas of the brain in patient with schizophrenia via resting-state fMRI.…”
Section: Antipsychotic Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keedy et al (2009) also found an increase in bilateral supplementary eye fields, left frontal eye fields, and bilateral cerebellum functional activity during visual attention and sensorimotor tasks and a decrease activity in other distributed brain regions in patients treated with risperidone, ziprasidone, or haloperidol. Miyazawa et al (2022) noted that that clozapine prolongs cortical silent period (the interruption of voluntary muscle contraction following a motor-evoked potential triggered by transcranial magnetic stimulation over the primary motor cortex) due to increase GABA transmission with GABA B receptors. Sarpal et al (2015) examined the association between antipsychotic treatment (e.g., aripiprazole or risperidone) and activity changes in striatal areas of the brain in patient with schizophrenia via resting-state fMRI.…”
Section: Antipsychotic Medicationsmentioning
confidence: 99%
“… Miyazawa et al (2022) noted that that clozapine prolongs cortical silent period (the interruption of voluntary muscle contraction following a motor-evoked potential triggered by transcranial magnetic stimulation over the primary motor cortex) due to increase GABA transmission with GABA B receptors.…”
Section: Effect Of Therapiesmentioning
confidence: 99%
“…An impaired ability to filter external auditory sensory information mediated by altered GABA B receptor firing has been associated with schizophrenia [ 117 , 118 ]. Specifically, an increase in the cortical silent period directly correlated with GABA function was observed in clozapine-treated patients compared to other antipsychotics [ 119 , 120 ], suggesting clozapine’s ability to improve signal-to-noise discrimination [ 121 ], potentially through the potentiation of GABA B -mediated inhibitory transmission [ 119 , 122 ]. Through X-ray crystal structure analysis, a recent study demonstrated that clozapine binds directly to the GABA B similarly to baclofen, a GABA B receptor agonist proposed as a non-canonical antipsychotic [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of clozapine on preexistent excitation-inhibition imbalance in schizophrenia has been studied only in a few TMS studies, and the results are inconsistent. Cross-sectional studies demonstrated shorter CSP durations in unmedicated or non-clozapine antipsychotic users compared with clozapine users 18,37,38 . Short-interval intracortical inhibition was not different between healthy controls, unmedicated patients, and clozapine users in one study 18 .…”
mentioning
confidence: 86%